Bone-protective effects of deer-hide gelatin in cyclophosphamide-induced osteoporosis rats - Mao, Hongyun; Zhao, Xinyue; Mo, Shaoqin; Wang, Haili; Liu, Rui; Xie, Yu; Huang, Yong; Zheng, Yunfeng; Hua, Yongqing (Frontiers in Pharmacology, 2025)
Chemotherapy is a cornerstone of cancer treatment, but its adverse effects, particularly those related to the cardiovascular and skeletal systems, are drawing more attention. According to studies, the PI3K/AKT signaling pathway may be involved in myelosuppression and cardiotoxicity, two types of multi-organ damage caused by chemotherapy. Despite the absence of thorough research, deer hide gelatin (DHG), a traditional Chinese medicine high in collagen, has shown promise in the prevention and treatment of skeletal and hematological disorders. This study aimed to evaluate the protective effects of DHG on chemotherapy-induced osteoporosis (OP) in rat bone tissue, as well as the material basis and mechanisms of its anti-OP activity. The results showed that DHG reversed the decrease in bone mineral density induced by chemotherapy, improved bone biomechanical properties, and ameliorated bone microstructure. DHG promoted the expression of the osteoblast-related indicators BALP and P1NP while suppressing the expression of the osteoclast-related marker TRACP-5b. Protein mass spectrometry screening was used to find putative anti-OP bioactive peptides. According to network pharmacology predictions, the PI3K signaling pathway may be the mechanism by which the active peptides in DHG produce their anti-OP actions. Additionally, immunofluorescence investigation demonstrated that DHG inhibited MMP9 expression while increasing RUNX2 expression. In vitro experiments also confirmed that DHG active peptides promoted bone formation by activating the PI3K/AKT/ERK signaling pathway, upregulating RUNX2 protein expression, and promoting osteoblast differentiation and mineralization. In conclusion, DHG has protective benefits against OP caused by chemotherapy. This also raises the possibility that DHG could be useful in the broader management of chemotherapy side effects (e.g., potentially related to cardio-oncology, considering the pathway’s important role in organs like the heart), warranting further investigation.